Organização lexical em bilíngues: uma investigação sobre os efeitos da proficiência em L2 na direcionalidade do priming encoberto de palavras cognatas e não cognatas - Fernandes, Maylton da Silva (2022)
There is an interest in Psycholinguistics in understanding how the lexicon or lexicons are represented and accessed in bilingual memory. Duñabeitia, Perea and Carreiras (2010) states in their study that simultaneous bilinguals, whose two or more languages were acquired at the same time during childhood, process both L1 and L2, or even both L1, in the same way regarless the direction of the stimulus, which would not be possible for late bilinguals whose L2 was acquired after childhood/adolescence. Also, there appears to be an asymmetry in bilingual lexical access regarding the direction of the linguistic stimulus. According to De Groot and Nas (1991), it is easier to access words from L2 when another one in L1 is presented first, but the same occurs much less even with speakers with a high level of proficiency, or may not even show, when an L2 word is displayed before an L1 word. This work aimed to investigate the facilitating effects of cognate and non-cognate words considering the direction of the linguistic input using a masked priming paradigm, as well as the lexical organization in late bilinguals, speakers of Brazilian Portuguese as their mother tongue and speakers of English as a foreign language, at intermediate and advanced levels. To this end, we selected 33 participants, 20 of them had an intermediate level of proficiency while the other 13 participants had an advanced level, according a placement test (NATION, 1990). This test was realized with a maximum time of 10 minutes, as indicated by Souza and Soares-Silva (2015), and we also applied a sociolinguistic questionnaire to check the participants’ linguistic background. Next, we applied an experimental task of masked priming, both in the L2-L1 direction and in the L1-L2 direction, involving words distributed between cognates and non-cognates, in addition to pseudowords used as pseudorandom distractors through the Mix program (VAN CASTEREN & DAVIS, 2006). According to the statistical analysis carried out based on the reaction time of the participants, a main effect was observed for the proficiency level, in which bilinguals with a higher level of proficiency had an average reaction time lower than those in the intermediate group. A significant effect was also observed in relation to the conditions of experimental words and pseudowords, with the reaction time for cognate and non-cognate words being shorter than the time for pseudowords. Furthermore, we observed significant effects in both priming directions, as well as observed priming effects in intermediate late bilinguals. In general, the results found are in line with the priming asymmetry mentioned by De Groot and Nas (1991), as well as corroborate the statement by Duñabeitia, Perea and Carreiras (2010), which says that unbalanced and non-simultaneous bilinguals process the L2 differently from the L1. Even so, the data obtained bring new light to the discussion about lexical processing in late bilinguals in the light of new models of language processing.